The immunology underlying tuberculosis - Hawn, Thomas R. (Henry Stewart Talks, 2022)
The immunologic challenges of tuberculosis and the gaps in knowledge, Tuberculosis and innate immunity, Mycobacterium tuberculosis and how it affects macrophages, granulomas, neutrophils and DCs, Tuberculosis and adaptive immunity, The role of IFNgamma, The T-cell response and immunodiagnostics, The progress of TB vaccines, Host-directed therapies